Assessment of heavy metals concentration in Gelama fish and water at Kuala Selangor and its potential health risk to human / Rabiatul Adawiyah Abdul Rahim and Nasaruddin Abd Rahman - Abd Rahman, Nasaruddin; Abdul Rahim, Rabiatul Adawiyah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Consumption of bioaccumulation heavy metals in fish had been found to cause severe health effect. This study was conducted in order to evaluate the concentration of selected heavy metals (Copper, Lead, Zinc, Cadmium) in the Gelama fish (Tigertooth Croaker) and water at Kuala Selangor estuary. This study also aimed to estimate the potential health risks through ingestion of this fish. The result showed the order of level concentration of metals studied found in Gelama fish was Zn > Cu > Cd > Pb. The study indicated that the concentration of these metals is below the permissible limit stated by Malaysian Food Regulation 1985. However, the concentration of Cd and Pb were slightly higher than Food and Agriculture Organization (FAO, 1984) but within the Malaysian government limits. Zn concentration was found to be significantly higher in the Gelama fish (p<0.05) in all sampling stations. For water samples, the result showed the concentration of metals studied was in the order of Zn>Cu>Pb>Cd. Target hazard quotient was calculated to determine the potential health risks associated with the heavy metals. The result showed that the THQ value was <1, which revealed that no adverse health effects expected from the consumption of fish at Kuala Selangor estuary. Hence, it can be concluded that Gelama fish caught at Kuala Selangor are safe to be consumed. However, a public awareness and continuous monitoring on heavy metals content in aquatic life should be done in order to reduce the potential health effect from the consumption of contaminated aquatic organisms.